2017
DOI: 10.1080/01463373.2017.1286363
|View full text |Cite
|
Sign up to set email alerts
|

Before Breaking Bad News: Relationships Among Topic, Reasons for Sharing, Messenger Concerns, and the Reluctance to Share the News

Abstract: Messengers are reluctant to reveal bad news, and this reluctance can hamper effective communication. With this investigation, we explore linkages among the topic of the news, messengers' reasons for sharing, messenger concerns about sharing, the locus of the news, and whether these variables associate systematically with messenger reluctance to share the news. Retrospective self-reports (N = 330) revealed that bad news occurred in reliable topic categories, which in turn related to reasons for sharing, how ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Fourth, we applied a research paradigm where either sender or receiver was responsible for the issue at hand, following the impression management model. Although disapproval and disappointments are the most salient topics regarding the delivery of bad news (Dibble & Sharkey, 2017), externally rooted positive or negative messages could pronounce relational goals even more in a desire for joint celebration or mutual comfort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourth, we applied a research paradigm where either sender or receiver was responsible for the issue at hand, following the impression management model. Although disapproval and disappointments are the most salient topics regarding the delivery of bad news (Dibble & Sharkey, 2017), externally rooted positive or negative messages could pronounce relational goals even more in a desire for joint celebration or mutual comfort.…”
Section: Discussionmentioning
confidence: 99%
“…However, in negative situations, we assume that people choose channels with a higher buffer effect for self-locus than other-locus situations for two reasons: first, the negatively valenced episodes of our paradigm, "confess" and "accuse," represent two instances that Brown and Levinson (1987) characterize as primarily threatening the speaker's or the hearer's face, respectively (Wilson et al, 1998). Second, people reportedly feel more reluctant when they are themselves the locus of the situation (Dibble & Sharkey, 2017). Regarding positive situations, we expect a similar effect of locus for another two reasons: First, Brown and Levinson (1987) compared the face threat of bringing good news about oneself (because it also indicates little care for the other) with the delivery of bad news about the recipient, an act which reportedly elicits reluctance.…”
Section: Locus Of the Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have identified that effective communication of health related information to patients and their families can reduce violence against healthcare 7-9. However, most of the people are reluctant to communicate any potentially disturbing or stressful information; considering it to be “Bad News” 10,11. Breaking bad news may lead to disappointment, distress and aggression in the receiver(s) and has a high potential to provoke violence depending on contextual factors 10,11…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the people are reluctant to communicate any potentially disturbing or stressful information; considering it to be “Bad News” 10,11. Breaking bad news may lead to disappointment, distress and aggression in the receiver(s) and has a high potential to provoke violence depending on contextual factors 10,11…”
Section: Introductionmentioning
confidence: 99%